Rating behavior of football fans by Internet - Szczygielski, Dawid; Napierała, Marek; Gotowski, Rafał (Journal of Education, Health and Sport, 2017)
The aim of this article was to present the opinion of Internet users for football fans and their behavior. The research method was used diagnostic survey research in the form of a survey computer. 102 people were tested mostly in the age of 21-25 years. The research can draw the following conclusions: (1) Football stadiums should be better secured and protected by the relevant departments, (2) The colors and club merchandise is not a reliable indicator of fan devotion of his team, (3) These are the fans, the fans are cheering for is a sacred thing, (4) All acts of devastation to property and vandalism in football stadiums should be severely punished.